Primary structure of bovine pituitary secretory protein I (chromogranin A) deduced from the cDNA sequence. - Ahn, T G (1987)
Secretory protein I (SP-I), also referred to as chromogranin A, is an acidic glycoprotein that has been found in every tissue of endocrine and neuroendocrine origin examined but never in exocrine or epithelial cells. Its co-storage and co-secretion with peptide hormones and neurotransmitters suggest that it has an important endocrine or secretory function. We have isolated cDNA clones from a bovine pituitary lambda gt11 expression library using an antiserum to parathyroid SP-I. The largest clone (SP4B) (approximately equal to 1.6 kilobases) hybridized to a transcript of 2.1 kilobases in RNA from parathyroid, pituitary, and adrenal medulla. Immunoblots of bacterial lysates derived from SP4B lysogens demonstrated specific antibody binding to an SP4B/beta-galactosidase fusion protein (160 kDa) with a cDNA-derived component of 46 kDa. Radioimmunoassay of the bacterial lysates with SP-I antiserum yielded parallel displacement curves of 125I-labeled SP-I by the SP4B lysate and authentic SP-I. SP4B contains a cDNA of 1614 nucleotides that encodes a 449-amino acid protein (calculated mass, 50 kDa). The nucleotide sequences of the pituitary SP-I cDNA and adrenal medullary SP-I cDNAs are nearly identical. Analysis of genomic DNA suggests that pituitary, adrenal, and parathyroid SP-I are products of the same gene.